Trust and Perceived Value as Strategic Drivers in Indonesia Omnichannel Beautypreneurship - Alexandrina, Elke; Sumarwan, Ujang; Yuliati, Lilik Noor; Nurhayati, Popong (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study aims to analyse the factors influencing customer loyalty within the omnichannel skincare ecosystem, focusing on the role of online trust, customer satisfaction, and repurchase intention. A quantitative approach was employed, utilizing a survey method involving 233 respondents who had purchased skincare products through various channels (both online and offline). Data analysis was conducted using Structural Equation Modeling (SEM) with LISREL to examine the relationships among variables within the developed conceptual model. The findings indicate that perceived product quality and perceived risk significantly influence perceived value, whereas price perception does not directly impact consumers' perceived value. Additionally, online trust plays a crucial role in enhancing customer satisfaction but does not directly influence repurchase intention. Conversely, repurchase intention is the primary factor shaping customer loyalty, whereas customer satisfaction does not have a direct effect on loyalty. These findings emphasize that customer loyalty is not solely dependent on satisfaction but is more closely linked to repurchase intensity, which is influenced by trust and positive omnichannel shopping experiences. The implications of this study highlight the importance of customer experience-based marketing strategies, including product quality enhancement, information transparency, responsive customer service, and the implementation of loyalty programs to encourage repurchase intention. By understanding the key factors driving loyalty within the omnichannel ecosystem, skincare companies can design more effective marketing strategies to enhance customer retention and strengthen competitiveness in an increasingly dynamic market.